Peningkatan Wawasan Kebhinekaan Global Pekerja Migran Indonesia di Kampung Bharu, Kuala Lumpur Malaysia - Rejeki, Sri; Mahardhani, Ardhana Januar; Harmanto, Bambang; Prayitno, Harun Joko; Purnomo, Eko; Pratiwi, Anggia Suci; Karman, Supardi Yoga (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2023)
This community service activity aims to provide understanding to Indonesian Migrant Workers and their families in Kampung Bharu Kuala Lumpur Malaysia who are members of the Muhammadiyah-Aisiyah Branch Leadership (PRIMA) Kampung Bharu Kuala Lumpur Malaysia. The dedication method used in this activity is socialization, lectures and questions and answers. This service was held on Saturday, 24 December 2022. The socialization of global diversity insights took place at TPA 1 PRIMA Kampung Bharu, Kuala Lumpur, Malaysia. This community service activity has had a positive impact on the understanding of the PRIMA Kampung Bharu extended family, regarding the insight into global diversity, and how to coexist peacefully in other countries and tolerance internally and externally for Indonesian citizens living in Malaysia.